The Shadow of the Neolithic Revolution on Life Expectancy: A Double-Edged Sword - Raphaël Franck; Oded Galor; Omer Moav; Ömer Özak (Global Labor Organization (GLO), 2022)
This research explores the persistent effect of the Neolithic Revolution on the evolution of life expectancy in the course of human history. It advances the hypothesis and establishes empirically that the onset of the Neolithic Revolution and the associated rise in infectious diseases triggered a process of adaptation reducing mortality from infectious diseases while increasing the propensity for autoimmune and in ammatory diseases. Exploiting an exogenous source of variation in the timing of the Neolithic Revolution across French regions, the analysis establishes the presence of these con icting forces - the beneficial effects on life expectancy before the second epidemiological transition and their adverse effects thereafter.
Keywords: I10; I15; J10; N00; N30; O10; O33; Z10; 330; Life Expectancy; Health; Mortality; Neolithic Revolution; Epidemiological Transition; Infectious Disease; Autoimmune Disease; Diabetes; Crohn's Disease; HIV; COVID-19